2022
DOI: 10.1126/science.abj2637
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Dion-Jacobson 2D structure enables efficient and stable perovskite solar cells

Abstract: Directing efficient hole transport Surface defects in three-dimensional perovskites can decrease performance but can be healed with coatings based on two-dimensional (2D) perovskite such as Ruddlesden-Popper phases. However, the bulky organic groups of these 2D phases can lead to low and anisotropic charge transport. F. Zhang et al . show that a metastable polymorph of a Dion-Jacobson 2D structure based on asymmetric organic molecules reduced the energy barrier fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
218
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(235 citation statements)
references
References 45 publications
(36 reference statements)
4
218
1
Order By: Relevance
“…Unencapsulated cells MPP at 65 °C in N 2 for 400 h, drop by ≈12% 2020 [30] Cs 0.1 FA 0.9 PbI 3 20.23 Strain engineering _ _ Unencapsulated cells stored at 70% RH for 500 h, drop by <30% _ 2020 [31] Cs 0.17 FA 0.83 PbI 3 23.35 Crystal growth Unencapsulated cells aged at 85 °C and 15 ± 5% RH in the air for 500 h, drop by ≈20% _ _ _ 2021 [32] Cs x FA 1-x PbI 3 21.98 Crystal growth _ _ _ _ 2021 [33] Cs 2019 [42] FA 0.57 MA 0.43 PbI 2.87 Br 0.13 21.21 (Certified) Crystal growth _ _ _ _ 2019 [43] (FAPbI 3 ) x (MAPbBr 2019 [44] (FAPbI 3 ) 0.85 (MAPbBr 3 ) 0.15 20.7 (Certified) Strain engineering _ _ _ _ 2019 [45] (FAPbI 3 ) 0.95 (MAPbBr 2019 [46] (FAPbI 3 ) 0.97 (MAPbBr 2021 [47] (FAPbI 3 ) 0.97 (MAPbBr 2021 [48] (FAPbI 3 ) 0.94 (MAPbBr 2021 [49] (FAPbI 3 ) 0.95 (MAPbBr 2021 [50] (FAPbI 3 ) 0.9 (MAPbBr 3 ) 0.1 25.2 (Certified) Interface engineering _ _ Encapsulated cells stored at 30% RH for 3600 h, no drop _ 2021 [51] Cs 0.05 FA 0.81 MA 0. 2019 [52] 2019 [53] (Cs,FA,MA)Pb(I,Br) 3 20.87 (Certified) Additive Stored in N 2 for 1500 h, drop by ≈10% _ 2019 [54] Cs 0.07 FA 0.9 MA 0.03 Pb(I 0.92 Br 0.08 ) 2019 [55] Cs 0.05 (FA 0.92 MA 0.08 ) 0.95 Pb(I 0.92 Br 0.08 ) 3 22.3 (Certified) Crystal growth _ _ _ MPP with 420-nm UV filter in N 2 for 1000 h, no drop 2020 [56] Cs _ 2020 [57] (Cs,FA,MA)Pb(I,Br) 3 23.3 (Certified) Crystal growth _ _ _ _ 2020 [58] (Cs,FA,MA)Pb(I,Br) _ 2021 [62] Cs 2021 [63] Cs _ 2021 [66] Table 1.…”
Section: Unencapsulated Cells Aged At 85 °C In Darkmentioning
confidence: 99%
“…Unencapsulated cells MPP at 65 °C in N 2 for 400 h, drop by ≈12% 2020 [30] Cs 0.1 FA 0.9 PbI 3 20.23 Strain engineering _ _ Unencapsulated cells stored at 70% RH for 500 h, drop by <30% _ 2020 [31] Cs 0.17 FA 0.83 PbI 3 23.35 Crystal growth Unencapsulated cells aged at 85 °C and 15 ± 5% RH in the air for 500 h, drop by ≈20% _ _ _ 2021 [32] Cs x FA 1-x PbI 3 21.98 Crystal growth _ _ _ _ 2021 [33] Cs 2019 [42] FA 0.57 MA 0.43 PbI 2.87 Br 0.13 21.21 (Certified) Crystal growth _ _ _ _ 2019 [43] (FAPbI 3 ) x (MAPbBr 2019 [44] (FAPbI 3 ) 0.85 (MAPbBr 3 ) 0.15 20.7 (Certified) Strain engineering _ _ _ _ 2019 [45] (FAPbI 3 ) 0.95 (MAPbBr 2019 [46] (FAPbI 3 ) 0.97 (MAPbBr 2021 [47] (FAPbI 3 ) 0.97 (MAPbBr 2021 [48] (FAPbI 3 ) 0.94 (MAPbBr 2021 [49] (FAPbI 3 ) 0.95 (MAPbBr 2021 [50] (FAPbI 3 ) 0.9 (MAPbBr 3 ) 0.1 25.2 (Certified) Interface engineering _ _ Encapsulated cells stored at 30% RH for 3600 h, no drop _ 2021 [51] Cs 0.05 FA 0.81 MA 0. 2019 [52] 2019 [53] (Cs,FA,MA)Pb(I,Br) 3 20.87 (Certified) Additive Stored in N 2 for 1500 h, drop by ≈10% _ 2019 [54] Cs 0.07 FA 0.9 MA 0.03 Pb(I 0.92 Br 0.08 ) 2019 [55] Cs 0.05 (FA 0.92 MA 0.08 ) 0.95 Pb(I 0.92 Br 0.08 ) 3 22.3 (Certified) Crystal growth _ _ _ MPP with 420-nm UV filter in N 2 for 1000 h, no drop 2020 [56] Cs _ 2020 [57] (Cs,FA,MA)Pb(I,Br) 3 23.3 (Certified) Crystal growth _ _ _ _ 2020 [58] (Cs,FA,MA)Pb(I,Br) _ 2021 [62] Cs 2021 [63] Cs _ 2021 [66] Table 1.…”
Section: Unencapsulated Cells Aged At 85 °C In Darkmentioning
confidence: 99%
“…Also, 90% of the initial PCE was retained after 1000 h of 1‐sun operation at 40 °C in nitrogen. [ 106 ]…”
Section: Diammonium Cations For 2d Halide Organic–inorganic Perovskit...mentioning
confidence: 99%
“…Recently, Zhu et al have reported that the corporation of metastable DJ‐phase perovskite layer can achieve the stable PCE of 24.7% for 3D lead perovskites solar cells, due to the efficient hole transport in the DJ‐phase lead perovskites. [ 98 ] Mohite et al also reported the higher PCE of DJ‐phase perovskites than their RP‐phase analogous. [ 99 ] Despite the emerging research progress, the tin/germanium DJ‐phase perovskites have to face the another serious issue.…”
Section: Challenges and Perspectivementioning
confidence: 99%